Synthesis of palmyrolide A and its cis-isomer and mechanistic insight into trans-cis isomerisation of the enamide macrocycle - Philkhana, Satish Chandra; Seetharamsingh, B.; Dangat, Yuvraj B.; Vanka, Kumar; Reddy, D. Srinivasa (Chemical Communications, 2013)
Concise and protecting-group free synthesis of ent-palmyrolide A and (-)-cis-palmyrolide A were achieved starting from commercially available (S)-citronellal. The key fragment of palmyrolide A, ``(5S,7S)-7-hydroxy-5,8,8-trimethylnonanamide'', which makes up the most challenging part of the target molecule, was prepared in just three steps. A plausible mechanism for the trans-cis isomerization of the double bond in the macrocycle has been investigated.

Iodine-catalyzed aromatization of tetrahydrocarbazoles and its utility in the synthesis of glycozoline and murrayafoline A: a combined experimental and computational investigation - Humne, Vivek T.; Dangat, Yuvraj B.; Vanka, Kumar; Lokhande, Pradeep (Organic & Biomolecular Chemistry, 2014)
A new protocol for the aromatization of tetrahydrocarbazoles has been achieved using a catalytic amount of iodine, giving high yields. The role of iodine in the aromatization has been explained by DFT, and its wide scope is extended to the total synthesis of glycozoline and murrayafoline A. This method has proven to be tolerant of a broad range of functional groups.

Synthesis, crystal structure and in vitro DNA binding studies of combretastatin A-4 analogue - Rizvi, Masood Ahmad; Dangat, Yuvraj B.; Yaseen, Zahid; Gupta, Vivek; Khan, Khaliquz Zaman (Croatica Chemica Acta, 2015)
Synthesis of a novel Combretastatin A-4 analogue using Schiff's reaction of benzil and 4-aminoantipyrine has been achieved under solvent free conditions. The structure of compound was examined spectroscopically and confirmed from single crystal diffraction studies. The synthesized Combretastatin A-4 analogue was investigated for its DNA binding ability as the plausible mechanism for its antitumor activity. The binding propensity of the synthesized compound with calf-thymus (CT) DNA was monitored with absorption and emission spectrophotometric titrations. The calculations predict a binding constant of 7.24 x 10(4) for the complex of the synthesized compound with CT DNA which is comparable in magnitude to that of DNA binding of bactericidal drug enoxacin and typical intercalation indicator ethidium bromide (EB). Competitive binding studies of the synthesized compound with EB using fluorescence titration reveal that it displaces the DNA-bound EB and binds in intercalative mode which was further supported by circular dichroism (CD) spectroscopy. The probable site and binding energy of the compound with DNA was further theoretically investigated by molecular docking studies. The significant DNA binding ability of the synthesized Combretastatin A4 analogue as revealed from this study could be related to the anticancer activity of the Combretastatin A4.
Keywords: benzil; bio-physical; combretastatin A-4; crystal structure; DNA binding; ethidium bromide; fluorescence; phenazones

Complexation key to a pH locked redox reaction - Rizvi, Masood Ahmad; Dangat, Yuvraj B.; Shams, Tahir; Khan, Khaliquz Zaman (Journal of Chemical Education, 2016)
An unfavorable pH can block a feasible electron transfer for a pH dependent redox reaction. In this experiment, a series of potentiometric titrations demonstrate the sequential loss in feasibility of iron(II) dichromate redox reaction over a pH range of 0-4. The pH at which this reaction failed to occur was termed as a pH locked reaction. The comparative ability of 10 selected iron binding ligands with varied propensity for the redox potential modification of Fe(III)/Fe(II) redox couple to restore/unlock the pH locked redox reaction is shown using potentiometric titrations. The spectrophotometric speciation analysis of Fe(III) Tiron complexation with pH was carried out to explain the differing ability of EDTA and Tiron to unlock the reaction under different pH Conditions. The experiment illustrates how environmental, biological redox reactions avoid severe laboratory conditions to occur and can be explored in the design of novel redox systems for natural attenuation of environmental toxins to their non- or lesser-toxic forms. The experiment also demonstrates prudent laboratory practice for safe waste disposal.
Keywords: Analytical Chemistry; Aqueous Solution Chemistry; Coordination Compounds; Oxidation/Reduction; pH; Physical Chemistry; Potentiometry; Second-Year Undergraduate; Thermodynamics; Titration/Volumetric Analysis; Upper-Division Undergraduate

Crystal structure, computational studies, and stereoselectivity in the synthesis of 2-aryl-thiazolidine-4-carboxylic acids via insitu imine intermediate - Jagtap, Rohidas M.; Rizvi, Masood A.; Dangat, Yuvraj B.; Pardeshi, Satish K. (Journal of Sulfur Chemistry, 2016)
This article presents the synthesis of (2R/2S,4R)-2-aryl-thiazolidine-4-carboxylic acids via nucleophilic addition of L-Cysteine on aromatic aldehydes involving a yield and time-effective room temperature reaction in an aqueous DMSO medium in the presence of NaHCO3 as a base. The synthesized diastereomers were spectroscopically characterized and quantified for diastereomeric excess by liquid chromatography-mass spectrometry analysis. The impact of the type and position of substituent in aromatic aldehydes on reaction time, % yield, H-1 NMR shift at newly formed chiral center [C(2)-H], and diastereomeric excess (de%) have been investigated. A plausible mechanism for stereoselectivity via an in situ imine intermediate is proposed using real-time IR monitoring of the synthetic reaction based on the significant signals at 1597, 1593cm(-1) for imine (C=N) stretching. The imine mechanism for stereoselectivity was further supported by NMR studies of azomethine C-13 NMR signals at 159, 160ppm and by the single crystal structure of hitherto unknown (2S,4R)-3-(tert-butoxycarbonyl)-2-(2-hydroxyphenyl)thiazolidine-4-carbox ylic acid (3a) obtained as a major diastereomer in the synthesis of the butyloxy carbonyl (BOC) derivative of (2R/2S,4R)-2-(2-hydroxyphenyl)thiazolidine-4-carboxylic acid. The significant ortho-OH effect of phenolic hydroxyl group leading to strong hydrogen bondings plays a vital role in the formation of 2S,4R BOC derivative stereoselectively. The frontier molecular orbitals, possible electronic excitations, IR band characterizations, and reactivity parameters of newly reported compound (3a) have been predicted using quantum chemical descriptors from density functional theory. The theoretical exploration of experimental spectra using time-dependent DFT indicated a (-*) transition between HOMO and LUMO in the ultraviolet region.
Keywords: 2-aryl-thiazolidine-4-carboxylic acids; density function theory; frontier molecular orbitals; imine intermediate; X-ray crystal structure

Exploring activity differences between the hydroformylation catalysts: Insights from theory - Dangat, Yuvraj B.; Rizvi, Masood Ahmad; Pandey, Pippalad; Vanka, Kumar (Journal of Organometallic Chemistry, 2016)
Hydroformylation catalysis is the most important homogeneous catalysis process of the current day. The current computational investigation aims to understand the nature of the hydroformylation process when monodentate ligands are employed. The complete catalytic cycle for different monodentate ligands bound to the rhodium center has been studied with full quantum chemical calculations, with density functional theory (DFT). To the best of our knowledge, this is the first systematic investigation of the relative free energy surfaces for mono-coordinate monodentate and bi-coordinated monodentate ligands in hydroformylation catalysis. The results indicate that the barriers are lower for the mono-coordinate monodentate species in comparison to the bi-coordinate monodentate, for all the ligand cases studied, indicating higher activity for the mono-coordinate monodentate active species. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Density functional theory (DFT) calculations; Hydroformylation; Monodentate; Rhodium

Exploring the reducing role of boron: added insights from theory - Dangat, Yuvraj B.; Vanka, Kumar (Dalton Transactions, 2016)
Carbon-carbon coupling in CO molecules is a challenging proposition, and very few main group complexes have been shown to effect this process. A recently reported triply bonded diboryne system (1) is notable for coupling four CO molecules to produce a (bis) boralactone species. The current full quantum chemical computational investigation with density functional theory (DFT) provides important insights into the nature of the CO coupling process by triply bonded diboryne systems. The complete reaction pathway leading to the formation of the (bis) boralactone has been determined. Factors that make this system so successful in coupling CO groups have been elucidated, and pertinent issues, such as why the coupling process stops after four CO additions, have been explored. Also, importantly, insights have been gained through the natural bond orbital (NBO) analysis into how the back-donation from diboryne activates CO.

Mechanistic insights into pincer-ligated palladium-catalyzed arylation of azoles with aryl Iodides: evidence of a Pd-II-Pd-IV-Pd-II pathway - Khake, Shrikant M.; Jagtap, Rahul A.; Dangat, Yuvraj B.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2016)
Pincer-based (R2POCNR′2)PdCl complexes along with CuI cocatalyst catalyze the arylation of azoles with aryl iodides to give the 2-arylated azole products. Herein, we report an extensive mechanistic investigation for the direct arylation of azoles involving a well-defined and highly efficient (iPr2POCNEt2)PdCl (2a) catalyst, which emphasizes a rare PdII–PdIV–PdII redox catalytic pathway. Kinetic studies and deuterium labeling experiments indicate that the C–H bond cleavage on azoles occurs via two distinct routes in a reversible manner. Controlled reactivity of the catalyst 2a underlines the iodo derivative (iPr2POCNEt2)PdI (3a) to be the resting state of the catalyst. The intermediate species (iPr2POCNEt2)Pd-benzothiazolyl (4a) has been isolated and structurally characterized. A determination of reaction rates of compound 4a with electronically different aryl iodides has revealed the kinetic significance of the oxidative addition of the C(sp2)–X electrophile, aryl iodide, to complex 4a. Furthermore, the reactivity behavior of 4a suggests that the arylation of benzothiazole proceeds via an oxidative addition/reductive elimination pathway involving a (iPr2POCNEt2)PdIV(benzothiazolyl)(Ar)I species, which is strongly supported by DFT calculations.

Reductive nitrosylation of nickel(II) complex by nitric oxide followed by nitrous oxide release - Ghosh, Somnath; Deka, Hemanta; Dangat, Yuvraj B.; Saha, Soumen; Gogoi, Kuldeep; Vanka, Kumar; Mondal, Biplab (Dalton Transactions, 2016)
Ni(II) complex of ligand L (L = bis(2-ethyl-4-methylimidazol-5-yl)methane) in methanol solution reacts with an equivalent amount of NO resulting in a corresponding Ni(I) complex. Adding further NO equivalent affords a Ni(I)-nitrosyl intermediate with the NiNO(10) configuration. This nitrosyl intermediate upon subsequent reaction with additional NO results in the release of N2O and formation of a Ni(II)-nitrito complex. Crystallographic characterization of the nitrito complex revealed a symmetric eta(2)-O,O-nitrito bonding to the metal ion. This study demonstrates the reductive nitrosylation of a Ni(II) center followed by N2O release in the presence of excess NO.